Faktor-Faktor yang Menentukan Keberhasilan Koperasi di Sektor Perdagangan dan Perindustrian di Kabupaten Probolinggo - Deddy Junaedi; Erinda Sulistiana; Evi Sri Wulandari; Indah Nurlaili Safitri; Sephia Eka Amalia Putri; Winda Wati; Raudatul Jannah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to identify the factors that determine the success of cooperatives in the trade and industrial sectors in Probolinggo Regency. Cooperatives have an important role in the local economy, especially in supporting trade and small industrial activities. This research uses a quantitative approach with a survey method involving cooperative entrepreneurs in the region. The variables tested include management, capital, human resource capacity, access to markets, and government policy support. The research results show that good managerial factors, ability to adapt to the market, and government policy support significantly influence the success of cooperatives in this sector. On the other hand, limited capital and the low quality of human resources are the main obstacles in developing cooperatives. It is hoped that this research will provide insight for cooperative managers, policy makers and related parties in developing more efficient and sustainable cooperatives in Probolinggo Regency.